Penerimaan diri remaja dengan orang tua bercerai: Menguji peran dukungan sosial dan konsep diri - Ferly Tiara Putri; IGAA Noviekayati; Amherstia Pasca Rina (INNER: Journal of Psychological Research, 2023)
Abstract This research was conducted with the aim of knowing the relationship between social support and self-concept on the self-acceptance of adolescents with divorced parents in Surabaya. The sample in this study were 72 teenagers with divorced parents in Surabaya. The sampling technique in this study was using purposive sampling. Measuring tools used in this study self-acceptance scale, social support scale, and self-concept scale. The data analysis technique used in this research is Spearman's Rho. Based on the data analysis conducted, it shows that 1) There is a positive relationship between social support and self-acceptance. This means that the higher the social support, the higher self-acceptance in adolescents; 2) There is a positive relationship between self-concept and self-acceptance. This means that the higher the self-concept, the more self-acceptance in adolescents; 3) There is no positive relationship between social support and self-concept with self-acceptance in adolescents. Therefore, the first and second hypotheses can be accepted, while the third hypothesis cannot be accepted. Keywords: Social Support; Self concept; Accepting yourself